Integrasi Nilai Keagamaan dan Nasionalisme: Studi Peran Banser Nahdlatul Ulama di Kecamatan Karangpucung: Integration of Religious Values and Nationalism: Study of the Role of Banser Nahdlatul Ulama in Karangpucung District - Nela Amalia; Reviana Intan Sari (CV Omah Kreator, 2025)
This article examines the role of Barisan Ansor Serbaguna (Banser) in fostering nationalism in Karangpucung District. As a semi-autonomous body under Gerakan Pemuda Ansor affiliated with Nahdlatul Ulama (NU), Banser has made significant contributions in safeguarding the integrity of the Unitary State of the Republic of Indonesia (NKRI), promoting the values of religious moderation, and building social harmony within multicultural communities. This study employs a qualitative descriptive approach, utilizing data obtained through field observations and in-depth interviews. The findings reveal that Banser plays a vital role in maintaining public order, countering radical ideologies, and instilling national values in society. Despite facing internal challenges such as financial limitations and familial responsibilities, as well as external skepticism regarding its relevance, Banser continues to carry out its duties through cultural approaches and selfless public service. These findings affirm that Banser is not merely a religious-based security force but also a vital civic institution that strengthens grassroots nationalism